Penggunaan Informasi Akuntansi, Peran Pemerintah Dan Kinerja Pedagang Sate Ikan Tanjung Masa Pandemi Covid-19 - Ni Nyoman Yuliati (Politeknik Keuangan Negara STAN, 2020)
The impact of pandemic covid-19 felt also by traders Tanjung fish satay in North Lombok. Lack of buyers causes some traders not to sell until conditions improve.This study aims to examine and analyze the effect of the use of accounting information and the role of the government on the performance of Tanjung fish satay traders during the covid-19 pandemic. The population in this study are all Tanjung fish satay traders with a total of 50 traders in the Tanjung market area, highway Tanjung or along the road to the center of North Lombok City. The sample was determined by using the Slovin formula with the sampling technique, namely incidental sampling. The number of samples that can be analyzed is 30 samples. Data were analyzed by multiple linear regression with SPSS 25 software. The results prove that the use of accounting information has a positive and insignificant effect on the performance of Tanjung fish satay traders. Meanwhile, the government's role has a positive and significant effect on the performance of Tanjung fish satay traders.Tanjung fish satay traders recognize the importance of using accounting information but have not been able to apply it due to limited human resources.